1994
DOI: 10.1002/app.1994.070531307
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of methacrylic acid–ethyl acrylate copolymers

Abstract: SYNOPSISCopolymerization of methacrylic acid (MAA) and ethyl acrylate (EA) was performed in aqueous medium in the presence of an emulsifier with MAA as the major component (53.7-82.3 mol % ) . Emulsion stability was studied as a function of concentration and the nature of the emulsifier (ionic or nonionic). Copolymers were characterized using IR and 'H-NMR spectroscopy. 13C-NMR spectra of MAA-EA copolymers have been discussed in terms of their triad monomer sequence distributions. Reactivity ratios of the MAA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…By copolymerizing styrene with other monomers such as acrylates, the deficiencies of polystyrene are tempered, and desirable properties can be achieved. 2,3 Copolymers of hydrophobic monomers like styrene, alkyl acrylates, and acrylonitrile and small amounts (1-10%) of polar unsaturated carboxylated monomers like acrylic acid, methacrylic acid, and itaconic acid are products of commercial interest because of their applications in paints, adhesives, binders, thickeners, and so forth. 4 The preparation of adhesive tape by applying a mixture of 2-ethylhexyl acrylate (EHA), methacrylic acid, and methyl methacrylate (MMA) copolymer emulsion with other additives, on polypropylene (PP) has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…By copolymerizing styrene with other monomers such as acrylates, the deficiencies of polystyrene are tempered, and desirable properties can be achieved. 2,3 Copolymers of hydrophobic monomers like styrene, alkyl acrylates, and acrylonitrile and small amounts (1-10%) of polar unsaturated carboxylated monomers like acrylic acid, methacrylic acid, and itaconic acid are products of commercial interest because of their applications in paints, adhesives, binders, thickeners, and so forth. 4 The preparation of adhesive tape by applying a mixture of 2-ethylhexyl acrylate (EHA), methacrylic acid, and methyl methacrylate (MMA) copolymer emulsion with other additives, on polypropylene (PP) has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The polarity of an acid monomer radical formed in the core of the particles by a chain transfer mechanism can cause their migration to the aqueous phase, resulting in the reduction of the average number of radicals per particle, n, and consequently, in the reduction of the overall rate of polymerization. 18 In spite of the low concentration of IA used in the present study, the assumption mentioned above would explain the lower polymerization rate observed for the reaction performed in the presence of this functional monomer (Fig. 1).…”
Section: Resultsmentioning
confidence: 61%
“…The composition of the copolymers was calculated6 by measuring the intensity ( I ) of the peak attributed to OCH 2 (d) protons of EA at δ 4.0 and then subtracting the contribution of EA from the multiplet of methyl protons of MAA and EA (a + a′). This value represents the contribution of the methyl protons of MAA units.…”
Section: Resultsmentioning
confidence: 99%